2021
DOI: 10.3390/life11121437
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the CREB Protein Family Members and the Related Transcription Factors in Radioresistance Mechanisms

Abstract: In the framework of space flight, the risk of radiation carcinogenesis is considered a “red” risk due to the high likelihood of occurrence as well as the high potential impact on the quality of life in terms of disease-free survival after space missions. The cyclic AMP response element-binding protein (CREB) is overexpressed both in haematological malignancies and solid tumours and its expression and function are modulated following irradiation. The CREB protein is a transcription factor and member of the CREB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 151 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have suggested that ATF5 plays important roles in cell survival, proliferation, and differentiation. 41 , 42 To verify the idea that ATF5 may be involved in the impaired differentiation of Rictor-deleted myeloid progenitors, the sorted WT LSKs were subjected to nucleofection with Cas9 protein and either ATF5 single guide RNA (sgRNA) or negative control sgRNA. The progenitors were then cultured in the presence of IL-3, IL-6, and M-CSF for 5-6 days.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that ATF5 plays important roles in cell survival, proliferation, and differentiation. 41 , 42 To verify the idea that ATF5 may be involved in the impaired differentiation of Rictor-deleted myeloid progenitors, the sorted WT LSKs were subjected to nucleofection with Cas9 protein and either ATF5 single guide RNA (sgRNA) or negative control sgRNA. The progenitors were then cultured in the presence of IL-3, IL-6, and M-CSF for 5-6 days.…”
Section: Resultsmentioning
confidence: 99%
“…CREB is a basic region transcription factor because it possesses a leucine zipper domain (bZIP) that promotes dimerization and mediates its binding to DNA. Among them, CREBP1 (also known as ATF-2) is a highly homologous protein and also has a bZIP structure [18]. As a first step, we investigated whether PFDN4 has the ability to regulate AURKA expression.…”
Section: Pfdn4 Regulates Breast Cancer Chemotherapy Resistance Throug...mentioning
confidence: 99%
“…1B, a putative motif for the cAMP response element (CRE) with a consensus sequence of 5′-TGACGTCA-3′ [22][23][24] was found from −83 to −76 in the FLT1 5′-flanking region. The cAMP response element binding protein (CREB)/activated transcription factor (ATF) family that binds to the CRE motif is known to play important roles in cell survival, proliferation, differentiation, apoptosis, and adaptive responses [25,26]. To determine whether CRE is important for FLT1 promoter activity, pFLT1-Luc (−90/+8) containing one mutated CRE was transfected into the four trophoblast cell lines.…”
Section: Identification Of Transcriptional Regulatory Elements Of The...mentioning
confidence: 99%